2022
DOI: 10.3389/fmicb.2022.902476
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Influenza and Other Respiratory Viruses in Hospitalized Patients Alongside the SARS-CoV-2 Pandemic

Abstract: Influenza A and other respiratory viruses, circulate each winter and cause respiratory illness that can lead to severe complications in hospitalized patients. During the COVID-19 pandemic, only a few cases of respiratory viruses were detected in Israel. Our study applied RT-PCR to examine 13,674 samples collected from patients hospitalized with respiratory symptoms in 2019, 2020, and 2021 and the first half of the 2022 winter. A sharp increase in influenza A(H3N2) cases was observed in winter 2021-2022 as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Person-to-person infection results from the introduction of the infected stool/mucus into an uninfected person through the oral cavity. This assumption coincides with reports of other respiratory viruses [ 20 , 21 ] that were attenuated during the pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Person-to-person infection results from the introduction of the infected stool/mucus into an uninfected person through the oral cavity. This assumption coincides with reports of other respiratory viruses [ 20 , 21 ] that were attenuated during the pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…17 The BA.1-and BA.5-induced interferon responses generated an antiviral state that protected infected cells from super-infection with influenza A viruses, showing that the Omicron-induced interferon response is of functional relevance. Our analysis of the spread of influenza-like illnesses during the Delta and BA.1 infection waves (Figure S6) and a number of additional studies [31][32][33][34][35] suggest that Omicron may interfere with influenza A virus transmission. However, these are correlations that need to be considered with care, and a causative relationship remains to be established.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, three further studies reported a decrease of influenza A virus infections when the Delta variant was replaced by the Omicron variant. [31][32][33] Additional studies found that Omicron patients were less likely to be coinfected with influenza A viruses than Delta patients 34 and that an H3N2 outbreak in Brazil only occurred after a decline in Omicron cases. 35 Notably, such observations do not provide conclusive evidence on a potential impact of Omicron circulation on influenza A virus spread.…”
Section: The Ba1-induced Antiviral State Is Primarily Mediated Via Ty...mentioning
confidence: 97%
“…Non-pharmacological preventive measures that had been applied during the COVID-19 pandemic were relaxed in the 2021–2022 season, resulting in an intense circulation of SARS-CoV-2 [ 20 , 21 ], and this virus displaced other respiratory viruses like influenza or RSV, which circulated scarcely [ 7 , 8 , 16 , 22 ]. Similarly, SARS-CoV-2 was the more frequent virus detected among deceased persons.…”
Section: Discussionmentioning
confidence: 99%